UTILIZATION AND MAINTENANCE OF HOUSE PAWNED AS A FIKIH PERSPECTIVE - Neng Eri Sofiana (Mu'amalat: Jurnal Kajian Hukum Ekonomi Syariah, 2020)
In Cianjur, West Java, to be precise, in the area of Cipanas District, there was an additional alternative to get the house temporary besides rented houses, namely pawned houses which are also in great demand because the payment will be recovered after the time the agreement ends. In Islam, there are differences of scholars’ opinions regarding the use of pawned goods, and many even state clearly that the use of pawned goods is not allowed. Then with field research and a qualitative descriptive approach with inductive data analysis methods, this paper will look at the legal status of a pawned house that is used as a residence and how to maintain the pawned house. It is found that the trend of looking for a pawned house and occupy it as a residence in Cianjur has been found for a long time, even now it can still be easily found. This happens because of the dense population with land which is also widely used for settlements, tourist attractions, accommodation, shops, and others. In addition, many empty villa buildings are also being promoted as a pawned house. As a result, this transaction becomes valid and can be carried out because the use of the pledged property in this case the pawned house as a residence has received permission from rahin and is in accordance with the initial agreement. If the pawned house is damaged due to the negligence of murtahin, then he is obliged to repair or replace it, but if it is damaged due to the length of time it becomes Rahin's responsibility.